Creativity identity in Colombia: the advertising creatives' perspective. Issue 6 (2nd November 2017) - Roca, David; Wilson, Bradley; Barrios, Andres; Muñoz-Sánchez, Omar
ABSTRACT: This exploratory paper analyses the way in which context influences advertising creativity practices. To establish the role of context, this paper utilized both Social Identity theory and Systems Model of Creativity. Twenty four in-depth interviews with top creative directors of the main advertising agencies in Colombia (Latin America) were collected. Findings suggest the Colombian creative identity is under construction. This identity is influenced by the broader Colombian social context including the unique business characteristics of the country's communications industry, the level of economic hardship experienced by the population, and the actual social conflict lived situation. These findings extend the Systems Model of Creativity to include social hardships and industry level characteristics. Several practical implications not only in relation to Colombia, but also the broader global advertising industry are presented.